Variational analysis of cracking in general composite laminates subject to triaxial and bending loads. (1st May 2020) - Hajikazemi, M.; McCartney, L.N.; Ahmadi, H.; Van Paepegem, W.
Abstract: A robust variational approach is first developed for predicting stress/displacement fields and effective thermo-elastic constants in a laminate with arbitrary lay-up, containing uniformly spaced ply cracks, subject to general triaxial and bending loads when the effects of thermal residual stresses are also considered. The methodology extends some previously developed variational approaches so that general non-symmetric lay-ups (not only cross-ply) under through-thickness loading conditions can be analyzed. Secondly, an approximate methodology is introduced which enables the approach to predict all effective thermo-elastic constants of laminates having non-uniformly spaced ply cracks, including new types of constant required to account for out-of-plane loading. Thirdly, some novel inter-relationships among effective thermo-elastic constants of cracked and uncracked general laminates are obtained showing that just three macroscopic parameters define the dependence of all relevant laminate constants (thirty five) on the state of cracking. The results are compared with those obtained from finite element methods, experiments and other high accuracy models.